2014
DOI: 10.1109/lsp.2014.2308591
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-Independent QRS Detection Using the Dynamic Plosion Index

Abstract: Detection of QRS serves as a first step in many automated ECG analysis techniques. Motivated by the strong similarities between the signal structures of an ECG signal and the integrated linear prediction residual (ILPR) of voiced speech, an algorithm proposed earlier for epoch detection from ILPR is extended to the problem of QRS detection. The ECG signal is pre-processed by high-pass filtering to remove the baseline wandering and by half-wave rectification to reduce the ambiguities. The initial estimates of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The worst cases for each database are shown, and the median result for each set of the corpus. In this work we also evaluated the gqrs detector [1] and a threshold independent algorithm [6] under the rodent set. Results where S=72.1; P =61.2 for the gqrs, and S=74.5; P =87.4 for the threshold independent algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The worst cases for each database are shown, and the median result for each set of the corpus. In this work we also evaluated the gqrs detector [1] and a threshold independent algorithm [6] under the rodent set. Results where S=72.1; P =61.2 for the gqrs, and S=74.5; P =87.4 for the threshold independent algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that our scheme achieved higher sensitivity and comparable positive predictivity compared to other reported detection schemes. Note that both DPI [4] and WT [11] were tuned and evaluated solely on the MIT-BIH database. It demonstrated that our novel RSWT scheme has a robust cross-database performance.…”
Section: Qrs Detection Results On Mit-bih Databasementioning
confidence: 99%
“…For determining the position of ECG characteristic points several QRS complex detection and ECG delineation methods are used. Some methods focus on detection of QRS complexes [2]- [4], while others use empirical mode decomposition [3] and threshold-independent QRS detection algorithm [4]. However, most of the QRS detection methods cannot be straightforwardly applied to the detection of P and T waves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worth evaluating how the performance of a QRS detection algorithm varies with the number of measurements. To achieve this goal, the threshold-independent QRS detector proposed in [23] is used. The ground truth for the R peaks is determined by the QRS detection provided by the algorithm when using the original ECG signal as input.…”
Section: Qrs Detection Performancementioning
confidence: 99%